Elevating Village Financial Care: Igniting Excellence through Dynamic Education and Training in Work Motivation - Kudri, Wan Muhamad; Putra, Rizaldi (First Ciera Publisher, 2024)
This study aimed to assess and analyze the impact of motivation, organizational culture, and competence on the work commitment and performance of elementary school teachers in cluster 4 of Bengkalis District. The selection of this research topic was motivated by observed phenomena and issues concerning the relatively low levels of work commitment and performance among elementary school teachers in this particular cluster. The data collection method employed for this study was a questionnaire, distributed to all 145 civil servant teachers in elementary schools within cluster 4 of Bengkalis District, constituting the entire population. Through Google Form questionnaires filled out by all 145 respondents, SEM PLS analysis was conducted. The research findings indicated that the motivation variable significantly and positively influenced work commitment. Organizational culture exhibited a significant positive impact on work commitment. However, job competency had a significant negative impact on work commitment. In terms of performance, the motivation variable demonstrated an insignificant positive impact, while organizational culture showed an insignificant positive impact as well. On the other hand, job competency had a significant positive effect on performance. Intriguingly, work commitment was found to have a significant negative impact on teacher performance.